Housing Affordability and Property Overhang: A Study on B40 and M40 Homebuyers’ Decision - Tan, Soon Meng (2021)
Housing is one of the human’s basic need as it provides shelter to an individual person or family. However, the B40 and M40 income group were seen having challenges in attaining homeownership as there were mismatch of supply and demand of affordable housing, which eventually lead to property overhang. Notwithstanding certain B40 and M40 income group were affordable to own residential property at price RM300,000 and below, yet it was reported that such property overhang at the same time. Thus the paradox situation trigger the need for this study to understanding homebuyers’ expectation in mitigating or avoid mismatch of demand and supply, which lead to property overhang. This research aim to find out factors influencing B40 and M40 income group buying decision towards an affordable house in Malaysia and to investigate whether housing affordability is the major factor influencing the B40 and M40 income group buying decision towards an affordable house in Malaysia. There were 346 survey questionnaires distributed and return, however only valid 304 of the samples will be use. In analysing the data, 36 measurement variables were accepted in meeting the reliability and validity test. Thereafter, using the factor analysis, the variables were grouped into 7 components which has eigenvalues of more than 1. Thus, there were 7 determinant factors revealed from the analysis that influence the B40 and M40 income group buying decision towards an affordable house in Malaysia. In addition, the study also confirmed that the housing affordability is the major determinant factor influence the B40 and M40 income group buying decision towards an affordable house in Malaysia.